TANTANGAN DAN OPTIMALISASI PERAN LEMBAGA PELAYANAN-KEPERAWATAN PENDUDUK LANJUT USIA (LAPORAN PRAKTIKUM PENGALAMAN LAPANGAN JURUSAN PENGEMBANGAN MASYARAKAT ISLAM DI PANTI WREDA SITI KHADIJAH KOTA CIREBON) - Suryadi Suryadi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2019)
The phenomenon of increasing the number of elderly population has implications for development, including: the impact on the budget, the social and psychological situation of the individual elderly population and the social structure of society, fulfillment of basic rights in the health and welfare sector. One of the basic needs of the elderly is the caring fields, because of the proportion eldely population with morbidity is quitely still high. Therefore, the provision of professional and humane care services is a necessity which is at the same time an opportunity for institutions and organizations engaged in the social and community welfare sector. By implementing professional and accountable social welfare management, it will be an important solution in meeting nursing needs with its various models.